2019
DOI: 10.1186/s12964-019-0467-7
|View full text |Cite
|
Sign up to set email alerts
|

GREM1 is associated with metastasis and predicts poor prognosis in ER-negative breast cancer patients

Abstract: Background: In breast cancer, activation of bone morphogenetic protein (BMP) signaling and elevated levels of BMP-antagonists have been linked to tumor progression and metastasis. However, the simultaneous upregulation of BMPs and their antagonist, and the fact that both promote tumor aggressiveness seems contradictory and is not fully understood. Methods: We analyzed the transcriptomes of the metastatic 66cl4 and the non-metastatic 67NR cell lines of the 4T1 mouse mammary tumor model to search for factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Furthermore, eradicating the [30,31]. Moreover, Gremlin 1 promotes its stem cell maintenance in glioma and colorectal cancer [32,33], and upregulation of Gremlin 1 significantly correlated with induced stem cell markers and poor survival of estrogen receptor (ER)-negative breast cancer patients [8]. These previous results are conspicuously consistent with our present results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, eradicating the [30,31]. Moreover, Gremlin 1 promotes its stem cell maintenance in glioma and colorectal cancer [32,33], and upregulation of Gremlin 1 significantly correlated with induced stem cell markers and poor survival of estrogen receptor (ER)-negative breast cancer patients [8]. These previous results are conspicuously consistent with our present results.…”
Section: Discussionsupporting
confidence: 92%
“…Like functions of TGF-β in cancer microenvironments, BMPs and their receptors have implicated an essential role as a dual function, which has a tumor suppressor and promoter of tumor progression in cancer. For example, Gremlin 1 expression, BMP-antagonist, in an analysis of large patient cohorts significantly increased in tumor tissues of breast cancer patients [8]. Also, Gremlin 1 induces tumorigenesis of cancer cells by inhibiting BMP/SMAD signaling and associated poor prognosis of breast cancer patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem cell models derived from 16 acute myeloid leukemia (AML) samples demonstrated an extraordinary ability to predict the clinical outcome of AML (Eppert et al, 2011). Similarly, in breast cancer, colon cancer, gastric cancer, and non-small cell lung cancer, the stem cell gene profile model holds promise in redefining clinical outcome stratification and identifying reduced risk (Giampieri et al, 2013;Miao et al, 2017;Codony-Servat et al, 2019;Neckmann et al, 2019). Moreover, three miRNAs (miR-23a, miR-9-3p, and miR-27a) derived from the analysis of GSCs by gene expression profiling, grouped mesenchymal and proneural GBM patients into two different categories with significant survival differences (Marziali et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in LRRK2 gene have been demonstrated to be associated with autosomal-dominant Parkinson's disease [22,23]. Studies have revealed that single nucleotide polymorphism in LRRK2 gene have been related to Crohn's disease [24,25]. It is reported that LRRK2 gene is involved in a variety of cellular processes including cell transformation, proliferation and tumorigenesis, and is linked to various types of cancer [26,27].…”
Section: Discussionmentioning
confidence: 99%